2018
DOI: 10.5194/acp-18-1705-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atmospheric trace gases and particulate matter in Hangzhou, China

Abstract: Abstract. The Yangtze River Delta (YRD) is one of the most densely populated regions in China with severe air quality issues that have not been fully understood. Thus, in this study, based on 1-year (2013) continuous measurement at a National Reference Climatological Station (NRCS, 30.22 • N, 120.17 • E; 41.7 m a.s.l.) in the center of Hangzhou in the YRD, we investigated the seasonal characteristics, interspecies relationships, and the local emissions and the regional potential source contributions of trace… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 90 publications
2
26
0
Order By: Relevance
“…Similar reasons to PM could explicate these monthly patterns which are a combined effect of enhanced pollutant discharge and relatively stable synoptic conditions in winter. Last but not least, a stronger photochemistry reaction can remove the gases quickly from the atmosphere whereas it is least active and decelerates the transformation of primary gaseous pollutants during cold months [13,37]. Compared to that in 2014, the concentrations of PM 2.5 , PM 10 , SO 2 , and CO in 2015 exhibits a marked decline in almost four seasons owing to a series of policies released by local government, while NO 2 concentration in the autumn of 2015 shows the abnormal increase.…”
Section: Seasonal and Monthly Variationsmentioning
confidence: 99%
“…Similar reasons to PM could explicate these monthly patterns which are a combined effect of enhanced pollutant discharge and relatively stable synoptic conditions in winter. Last but not least, a stronger photochemistry reaction can remove the gases quickly from the atmosphere whereas it is least active and decelerates the transformation of primary gaseous pollutants during cold months [13,37]. Compared to that in 2014, the concentrations of PM 2.5 , PM 10 , SO 2 , and CO in 2015 exhibits a marked decline in almost four seasons owing to a series of policies released by local government, while NO 2 concentration in the autumn of 2015 shows the abnormal increase.…”
Section: Seasonal and Monthly Variationsmentioning
confidence: 99%
“…The focal city of this study is Hangzhou—one of the central cities of the Yangtze River Delta Urban Agglomeration. We explored its atmospheric environment and found that, as a tourist city, Hangzhou’s air quality condition was not satisfactory [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Liu et al [ 26 ] analyzed the atmospheric PM 2.5 concentration and variation in Hangzhou from 2011 to 2014 and concluded that the peak occurred in 2013 (52.2 µg m −3 ) and was closely related to motor vehicle emissions and changes in meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PAN was measured by a modified gas chromatography (Agilent 7890B, USA) equipped with electron capture detector, which has been described in our previous studies in details (Zhang et al, 2012a;Zhang et al, 2014;Zhang et al, 2015). Trace gases including O 3 , SO 2 , NO x , and CO were detected by a set of commercial trace gas analyzers (Thermo Environmental Instruments Inc., USA i-series 49i, 43i, 42i, and 48i), respectively (Zhang et al, 2018). Ambient VOCs were measured by using an on-line gas chromatography (Syntech Spectras Instrument Co., Ltd., The Netherlands) coupled with dual detectors (Photo Ionization Detector (PID) and flame ionization detector (FID) for quantifying C 2 -C 5 VOCs (GC955 series 811) and PID for detecting C 6 -C 12 VOCs (GC955 series 611).…”
Section: Observationsmentioning
confidence: 99%
“…Complex atmospheric pollution including particulate and photochemical pollution (ozone (O 3 ) and peroxyacetyl nitrate (PAN)) is a pervasive environmental issue in eastern China (Geng et al, 2007;Ding et al, 2013;Mo et al, 2015;Li et al, 2016;Zhang et al, 2018). Numerous mitigation strategies have been released by the Chinese government, such as the nationwide application of flue-gas desulfurization (FGD) devices in power plants after 2006 (Feng et al, 2014) and "Atmospheric Pollution Prevention and Control Action Plan" in 2013 (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%